Intellectual disability among Bhutanese refugees referred to psychiatric service of BPKIHS (Health Renaissance, 2017)
Background: Intellectual disability plays a significant role, especially in the field of rehabilitation. It becomes more important when people live in refugee camp for a long duration.Objective: To assess the level of intelligence and disability; and to sort out the illnesses comorbid with mental retardation in the Bhutanese refugees in eastern Nepal.Methods: Hospital based descriptive study was done using purposive sampling. Instruments used were: vineland social maturity scale, developmental screening test, seguin form board, standard progressive matrices and colored progressive matrices.Results: Samples were 42 with 64% females. Age range was 11-20 years. Among these referred cases, 45% had speech disorder and hearing loss and 31% had neurological disorders, including seizure disorders. Sixty-six percent had mild, 9% moderate and 19% severe mental retardation.Conclusion: Majority of the intellectually disabled Bhutanese refugees had mild mental retardation, followed by severe one. Seizure was a common co-morbidity in mental retardation. Health Renaissance 2015;13 (1):